Immunology of stroke: - safari, Anahid; safari, Rasool; Borhani-Haghighi, Afshin (Galen Medical Journal, 2016)
Stroke, a multifactorial disease, has distinct pathophysiologic mechanisms, among which inflammation plays a pivotal role. Various types of inflammatory cells, substances, and molecules emerge in the ischemic stroke. Neutrophils, Tcell subtypes, macrophages, microglial cells, dendritic cell, mast cells, asrocytes, as influential cell,Â  tumor necrosis factor_Î±, interleukin-17, interleukin-10, as released substances, andÂ  vascular cell adhesion molecule-1 (VCAM-1), leukocyte very late antigen-4 (VLA-4), and glial fibrillary acidic protein (GFAP), as cellular adhesion molecules. Lymphocytes’ invasion to the ischemic brain tissue occurs as the result of VLA-4Â  Ì¶ VCAM-1 interaction. Regarding Tcell subtypes, CD4+ cells have known detrimental effects in the ischemic area, while natural killer T cells (NKT cells) and Î³Î´ T cells have minor importance in the early stage of ischemia. While some studies proved the cerebroprotective impact of T regulatory cells, others refuted this by presenting a prominent harmful role of them. Bcells have important protective function by releasing IL-10. Neutrophils along with microglial cell, appearing as the first inflammatory cell in the ischemic tissue, and also macrophages deteriorate ischemia. Mast cells and dendritic cells are of great value in stroke progression. The resting astrocytes are neuroprotective, whereas the activated ones present detrimental function in the ischemic region by expression of GFAP. Hence, stroke consequences occur as the result of systemic inflammatory response. The more activation of this system, the poorer neurological outcomes would be observed. As expected, anti-inflammatory interventions in the experimental stroke in animals, have revealed successful results as less infarct size and attenuated neurological damages.